2016
DOI: 10.1016/j.jclinane.2015.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the C-MAC video laryngoscope to a flexible fiberoptic scope for intubation with cervical spine immobilization

Abstract: The C-MAC may offer an advantage over the FFS with respect to the time required to obtain glottic view and successful placement of the tracheal tube in patients requiring cervical spine immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
2
20
3
1
Order By: Relevance
“…It has many advantages such as similarities to the conventional laryngoscopy, and more familiarity to psychomotor skills [ 6 ]. A recent study reported that the C-MAC video laryngoscope offers an advantage over the flexible fiberoptic scope with respect to the time required to obtain a glottic view and successful placement of the tracheal tube in patients with cervical spine immobilization [ 7 ]. In addition, Shirgoska and Netkovski [ 8 ] suggested that video laryngoscopy can be easily learned and should be used for managing difficult airway situations in the operating room, as well as in the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…It has many advantages such as similarities to the conventional laryngoscopy, and more familiarity to psychomotor skills [ 6 ]. A recent study reported that the C-MAC video laryngoscope offers an advantage over the flexible fiberoptic scope with respect to the time required to obtain a glottic view and successful placement of the tracheal tube in patients with cervical spine immobilization [ 7 ]. In addition, Shirgoska and Netkovski [ 8 ] suggested that video laryngoscopy can be easily learned and should be used for managing difficult airway situations in the operating room, as well as in the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, we identified and retrieved 18 randomized clinical trials for inclusion evaluating 1972 patients ( Figure 1). Table 1 Three trials were judged to be at low risk of bias, 12-14 13 at unclear risk [15][16][17][18][19][20][21][22][23][24][25][26][27] and 2 at high risk. 28,29 Random sequence generation was assessed as low risk of bias in 16 trials, allocation concealment in 9 trials, completeness of outcome data in 8 trials, selective outcome reporting in 4 trials and other bias in 15 trials ( Figure 2 and Figure S1, Table S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the remaining 14 RCTs, [12][13][14][18][19][20][21][22][23][24][25][26]28,29 intubation was performed under general anesthesia after administration of sedative and neuromuscular blocking agents. Since the evaluated techniques were highly heterogeneous, we decided to perform two main meta-analytic comparisons focused on the devices commonly available in the operating room: (a) direct, traditional Macintosh laryngoscopy versus other techniques (three RCTs; Figure 2) and (b) videolaryngoscopy versus other techniques (five RCTs; Figure 3).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Perbedaan ini disebabkan oleh perbedaan subjek penelitian, yaitu pasien dengan variasi anatomis yang berbeda dan angka keberhasilan dalam penelitian ditentukan dengan 1 kali percobaan (first attempt intubation). 14 Angka keberhasilan intubasi yang tinggi mempergunakan purwarupa camera-bougie disebabkan oleh purwarupa ini memiliki kelenturan untuk dibentuk dan diarahkan seperti bougie dan memberikan visualisasi laring atau plica vocalis pada saat intubasi dilakukan. Kemampuan purwarupa camerabougie untuk memberikan gambar visual akan mengatasi kesulitan visualisasi laring saat laringoskopi direk yang merupakan penyebab utama penatalaksanaan jalan napas sulit.…”
Section: Subjek Dan Metodeunclassified